Depression and Anxiety Among Patients with Epilepsy: A Cross-Sectional Study in Saudi Arabia - Mohammed A. Aljaffer; Ahmad H. Almadani; Ayedh H. Alghamdi; Anas A. Alalwan; Fay H. Albuqami; Khalid O. Altowaijri; Lujain A. Alkhalaf; Faisal A. Alazmi; Shahad F. Aljeri; Hadel H. Alhaluli; Bandar N. Aljafen (Brain Sciences)
Background: Epilepsy is a major neuropsychiatric disorder affecting many people worldwide, with depression and anxiety being common comorbidities that impact the quality of life (QoL). This study aims to examine depression and anxiety in epileptic patients at a tertiary care hospital, King Khalid University Hospital (KKUH), Riyadh, Saudi Arabia. It also aims to assess participants’ QoL and explore associated risk factors. Methods: This cross-sectional study enrolled 400 participants using a convenience sampling technique. The study tool consisted of a questionnaire, the Arabic version of the Hospital Anxiety and Depression Scale, and the Arabic version of the Quality of Life in Epilepsy Inventory. Results: The results revealed that 48.25% of the participants exhibited depression, and 39.75% exhibited anxiety. There was a statistically significant association between depression and educational level, employment status, history of psychiatric disorders, epilepsy duration, and all subscales of the Quality of Life in Epilepsy Inventory (QOLIE-31). There was also a statistically significant association between anxiety and educational level, employment status, history of psychiatric disorders, epilepsy duration, and all subscales of QOLIE-31. The mean overall QOLIE-31 score was 60.21 ± 20.19, with educational level and employment status, among other factors, being significantly associated with QOLIE-31. Conclusions: Depression and anxiety are prevalent among epileptic patients, requiring routine screening. Supporting education and employment among epileptic patients also appears to be crucial. Strategies to improve QoL among this population should be developed.